Ventral tegmental area astrocytes orchestrate avoidance and approach behavior - J. A. Gomez (Nature Portfolio, 2019)
Astrocytes can dynamically control glutamate availability at specific active synapses through the glutamate transporter, GLT-1. Here, the authors show that astrocytes in the VTA selectively facilitate excitation of VTA GABAergic neurons to inhibit dopamine neurons and drive avoidance behavior via GLT-1.